Monitoring Network and Service Availability with Open-Source Software - Silver, T. Michael (Information Technology and Libraries, 2010)
Silver describes the implementation of a monitoring system using an open-source software package to improve the availability of services and reduce the response time when troubles occur. He provides a brief overview of the literature available on monitoring library systems, and then describes the implementation of Nagios, an open-source network monitoring system, to monitor a regional library system’s servers and wide area network. Particular attention is paid to using the plug-in architecture to monitor library services effectively. The author includes example displays and configuration files. Editor’s note: This article is the winner of the LITA/Ex Libris Writing Award, 2009.